Wyobrażenia i oczekiwania nauczycieli wobec przyszłości = Teachers` ideas and expectations about the future - Drożka, Wanda Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article shows the results of the research on teachers` personal, individual, and broader - global - expectations about the future. The study is an attempt to compare the social, life, and professional values of the currently working teachers with the values of the persons teaching 25 years ago. As the comparative material for the investigation, the author used the results of the research performed at the turn of 1989 and 1990. The research results suggest that despite numerous positive democratic changes at school, there still persists a kind of the "shortage syndrome", i.e. a poor atmosphere in interpersonal relations, in the school environment, and the social surroundings of schools.
Keywords: nauczyciele; badania; wyobrażenia o przyszłości; osobiste i globalne wartości; teacher; researches; ideas about the future; personal and global values